Secure IoT framework for authentication and confidentiality using hybrid cryptographic schemes - Ali, Salman; Anwer, Faisal (International journal of information technology (Singapore. Online), 2024)
IoTs are increasingly gaining popularity and prevalence due to their extensive applications across various domains. They gather data from the real environment and transmit it through the networks. Security is essential to prevent data alteration, misuse of data, unauthorized access, etc. Cryptography techniques are an efficient way to provide a security mechanism for stored data and data during transmission. The proposed secure model commences by authenticating the user and IoT and activating associated IoT devices that are subsequently, sent data to the cloud server. To ensure the secure transmission of IoT data, the technique utilizes Elliptic Curve Cryptography (ECC) in combination with Genetic Algorithm (GA) to generate keys. The data is encrypted using the generated key and the Advanced Encryption Standard (AES). Assessment and comparison are performed based on parameters such as key size, execution time, throughput, and avalanche effect. Experimental results show that the proposed model ensures the authentication and confidentiality of the data against unauthorized access and data expose. Moreover, the proposed approach is robust and performs better on selected parameters than state-of-the-art cryptographic algorithms such as Data Encryption Standard (DES) and Rivest–Shamir–Adleman (RSA).